Inequality in breastfeeding and complementary feeding practices in Argentina by household income level in 2018–2019 - Zapata, Maria Elisa (2024)
ABSTRACTIntroduction. Diet quality is a right related to survival, healthy growth, prevention of chronic diseases,and malnutrition in all its forms. The objective of this study was to analyze breastfeeding and feedingpractices in children younger than 2 years from urban areas of Argentina in 2018–2019 according totheir household income level.Population and methods. Secondary analysis of data of the Second National Survey on Nutrition andHealth (ENNyS2) of 2018–2019. Breastfeeding and complementary feeding indicators proposed by theWorld Health Organization (WHO) and the United Nations Children’s Fund (UNICEF) were analized.Data were stratified by household income level.Results. The analysis included 5763children younger than 24months old. Although 97% was ever breastfed,only 47% of infants younger than 6 months were exclusively breastfed the previous day and 48% continuedwith breastfeeding after 1 year old, with a higher prevalence in low-income children. The previous day,23% of children aged 6 to 23 months did not eat any fruit or vegetable, 60% consumed unhealthy foods,and 50% consumed sweet beverages. The consumption of sweet beverages and the absence of fruit andvegetables were higher in low-income households.Conclusion. The quality of children’s diet is far from the recommendations and is conditioned by income.Early initiation of breastfeeding, minimum dietary diversity, fruit and vegetable consumption are lowerand sweet beverage consumption is greater in impoverished sectors.